2020
DOI: 10.1088/1757-899x/884/1/012098
|View full text |Cite
|
Sign up to set email alerts
|

Complex geometry automotive muffler sound transmission loss measurement by experimental method and 1D simulation correlation

Abstract: A muffler is a device to attenuate noise from the exhaust. The muffler performance determined by the acoustic performance is called sound transmission loss (STL). This paper aims to measure the STL experimentally and correlated with the 1D simulation result. STL was measured using the impedance tube. Four-pole method (microphone) and two-load method were applied to measure the STL. The STL was also determined through the 1D simulation tools software. Three types of mufflers STL were measured; small expansion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Helmholtz resonator and pointed out that it can get good attenuation properties at three frequency harmonics of hydraulic flow pulsation. [23] Considering that the energy of hydraulic flow pulsation mainly distributes at the fundamental frequency and its first two harmonics. Fig.…”
Section: Fig 1 Structure Of Three 1-dof Helmholtz Resonatormentioning
confidence: 99%
“…Helmholtz resonator and pointed out that it can get good attenuation properties at three frequency harmonics of hydraulic flow pulsation. [23] Considering that the energy of hydraulic flow pulsation mainly distributes at the fundamental frequency and its first two harmonics. Fig.…”
Section: Fig 1 Structure Of Three 1-dof Helmholtz Resonatormentioning
confidence: 99%
“…Kalita and Singh studied in [11] the prediction of TL based on ANSYS software. Mohammad et al developed in [12] an experimental setup to measure the muffler TL using an impedance tube and 1D simulation. In his thesis [13], Olgar developed TMM and finite element modeling (finite element method-FEM) to predict the TL for industrial machinery.…”
Section: Introductionmentioning
confidence: 99%
“…In a hybrid muffler, Horoub investigated the results of joining tapered expansion chambers of various sizes (Guhan et al, 2018). Computational fluid dynamics (CFD) tests on these connected expansion chambers revealed that extensions on baffles decreased the pressure drop within the silencer in comparison to a single expansion chamber of comparable size (Mohammad et al, 2020). The transfer matrix representation, which has been extensively utilised in the past to assess and quantify the acoustical characteristics of flow system components, serves as the foundation for the mathematical formulation (Muhammad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%